Optimization of gelatin nanofabrication as a potential biocompatible nanocarrier - Nada A. Hussein; Ghada M. El Zaafarany; Mona M. A. Abdelmottaleb; Gehanne A. S. Awad (Archives of Pharmaceutical Sciences Ain Shams University)
Gelatin is a promising natural biomaterial used as a drug delivery system for various indications. It is a cheap, abundant and safe protein derived from collagen with proved biodegradation, biocompatibility and non-immunogenicity. According to its source, gelatin can be obtained by acid or alkaline hydrolysis, which affects its physicochemical properties. Gelatin B is more negatively charged than gelatin A, with respective isoelectric points (IEP) of 5 and 8.5. Different gelatin drug delivery systems have been obtained including microparticles, nanoparticles, fibers and hydrogels. Furthermore, gelatin has multiple functional groups which enable its crosslinking and other modulations to achieve specific targeting, improve and sustain drug action and control side effects. The scope of this study was to investigate the effect of various parameters affecting the obtainment of a stable gelatin nano-system. Four important factors were scrutinized using the double desolvation method: pH, type and method of addition of water miscible antisolvents and finally the polymer concentration. The obtained nanoparticles were evaluated for their particle size, polydispersity index and zeta potential.